ASME 2010 Conference on Smart Materials, Adaptive Structures and Intelligent Systems, Volume 2 2010
DOI: 10.1115/smasis2010-3615
|View full text |Cite
|
Sign up to set email alerts
|

Actuation Requirements of a Warp Induced Variable Twist Rotor Blade

Abstract: This paper examines a warp induced twist concept to obtain quasi-static large amplitude twist changes of helicopter or tiltrotor blades for performance benefits over diverse operating conditions. The concept presented in this paper has a cylindrical spar with rotating ribs, with the ribs attached to the skin which is slit along the trailing-edge. Warping the skin then produces twisting of the blade section, while bending loads are still transferred to the main spar. Warp actuation is implemented by rotating a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…The study in this article uses the reverse concept whereby directly applying a warping force along the beam span produces spanwise camber variation. The work builds on previous efforts where warp-twist coupling was utilized to vary wing twist in fixed-wing applications (Vos et al, 2008(Vos et al, , 2010, to helicopter rotor blade morphing (Mistry, 2008;Mistry et al, 2011;Thomas et al, 2008;Van Weddingen et al, 2010), and most recently to wind-turbine blade twist morphing (Lachenal et al, 2013). In particular, it represents a continuation and development of the authors' work in Mistry (2008) and Mistry et al (2011).…”
Section: Design Conceptmentioning
confidence: 90%
See 3 more Smart Citations
“…The study in this article uses the reverse concept whereby directly applying a warping force along the beam span produces spanwise camber variation. The work builds on previous efforts where warp-twist coupling was utilized to vary wing twist in fixed-wing applications (Vos et al, 2008(Vos et al, , 2010, to helicopter rotor blade morphing (Mistry, 2008;Mistry et al, 2011;Thomas et al, 2008;Van Weddingen et al, 2010), and most recently to wind-turbine blade twist morphing (Lachenal et al, 2013). In particular, it represents a continuation and development of the authors' work in Mistry (2008) and Mistry et al (2011).…”
Section: Design Conceptmentioning
confidence: 90%
“…While the rotor blade design in Mistry (2008) and Mistry et al (2011) was shown to be capable of producing large twist variation, it also had a couple of major limitations. The first was the significant reduction in blade bending and torsion stiffness associated with the circular spar and rotating ribs supporting the shell skin.…”
Section: Design Conceptmentioning
confidence: 98%
See 2 more Smart Citations
“…Creating a discontinuity in the skin, and thereby creating an open walled cross-section, reduces the torsional stiffness significantly. The actuated screw thread is able to resist torsion while enabling controlled twisting of the blade [25,26].…”
Section: Introductionmentioning
confidence: 99%